Evaluasi Penerimaan Retribusi Pariwisata dalam Meningkatkan Pendapatan Asli Daerah - Nadya Jennyharty Beta; Yosefina Andia Dekrita; Imelda Virgula Wisang (Universitas Nusa Nipa Maumere, 2026)
The tourism sector is a startegic domain with significant pontential to augment Local Own-Source Revenue (PAD) through the collection of tourism levies. However, the realization of this potential is often impeded by various implementation challenges. This study aims to evaluate the effectiveness of tourism levy revenue in enhancing the PAD of Sikka Regency. Employinng a descriptive qualitative methodology, data were collected through observation, documentation, and in-depth interviews. The findings reveal that while the implementation of tourism levies is underpinned by a clear legal framework and orderly administrative mechanisms for collection, recording, and reporting, the revenue realization remains suboptimal. This is evidenced by the achievement of only 47% of the designated target. Kiosk fees at the Snack and Souvenir Center emerged as the primary revenue contributor, whereas other levies, such as parking and recreation venue fees, contributed nothing due to a critical lack of on-site management personnel. This condition indicates that deficiencies in management and supervision are the principal obstacles to optimizing tourism levy revenue. Therefore, concerted efforts are imperative, including restructuring the collection system, appointing dedicated field managers, and fostering collaboration with third parties. These measures are crucial to harness the full potential of tourism levies and substantially support the growth of Sikka Regency’s Local Own-Source Revenue.